ANAK KORBAN KEKERASAN SEKSUAL AKIBAT KETIMPANGAN GENDER - Arsawati, Ni Nyoman Juwita; Gorda, AAA.Ngr. Tini Rusmini; Darma, I Made Wirya; Nandari, Putu Sawitri (Jurnal Legislasi Indonesia, 2019)
Every child has the rights to survive, grow and develop and protection from violence and discrimination. The protection of children's rights still has not got attention from various parties, such as the case of the junior high school student of class 9 in Jehem Village, Tembuku sub-district, Bangli regency, who had to drop out of school due to pregnancy as a result of the sexual violence. The sexual violence shows that women are still placed in a marginal position because of their gentle nature exploited by men to vent their desires. It can occur in the domestic and public sectors. The sexual violence in children can occur in their environment like the cases in which the parents raping the biological or stepchild and the sibling brother raping his sister. This position makes the children powerless in facing the unprotected treatments. Bali which has increasing number of children violence every year in each regency positions the government to work on the protection in the form of regulations and the involvement of customary institutions which will stated in awig-awig or perarem in each  pakraman village.